Achieving absolute decoupling? Comparing biophysical scenarios and macro-economic modelling results - Dominik Wiedenhofer; Marina Fischer-Kowalski (WWWforEurope, 2015)
Most economic models struggle to incorporate biophysical relationships between materials, energy and emissions, in order to appropriately deal with biophysical constraints of supply (and possibly also demand). After the incorporation of biophysical constraints, some functions produced surprising or even highly implausible results. These results have been checked against expert judgement of plausibility, some biophysical assumptions have been refomulated or removed to secure consistency, and some economic functions have been adjusted to take care of adequacy and plausibility of outcomes and model specifications. A number of efforts were made to check the consistency of economic modelling outcomes with some fundamental functional interdependencies on the biophysical level and against the biophysical scenarios presented in earlier papers (Milestones MS35 - published as WWWforEurope Working Paper no. 25; and MS36 - unpublished). This usually required extensive communication between research teams and the re-formulation of certain parameters, relationships and semi-empirical assumptions. Methodologically, such interdisciplinary cross-checking is a novel and time-consuming exercise. This process highlights the limitations of existing economic models to incorporate certain biophysical functional interdependencies, and vice versa the still very limited ability of biophysical models to explore ranges of flexibility imposed upon changing economic assumptions. Furthermore this ongoing collaboration showed that the specification of the baseline scenario and the semi-empirical assumptions about efficiency gains as well as developments of factor productivity and technical change are highly influential on the results of each scenario. Therefore a 'realistic' specification and critical reflection of the actual feasability of certain baseline trajectories is deemed necessary.
Keywords: Q3; Q4; Q5; 330; Beyond GDP; Biophysical constraints; CGE models; Ecological innovation; Economic growth path; Economic strategy; European economic policy; Full employment growth path; Industrial policy; Innovation policy; Macroeconomic disequilibria; Market economy with adjectives; Socio-ecological transition; Sustainable growth; Wealth